Coal-based carbon negative electrode material, preparation method thereof and sodium ion battery
Through the mixed grinding and carbonization of coal-based materials and biomass carbon, a coal-based carbon negative electrode material with high electrochemical performance was prepared, which solved the problem of poor performance of negative electrode materials in sodium ion batteries and achieved the high specific capacity and cycling performance of sodium ion batteries.
Patent Information
- Application Number
- CN202510001953.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
In the current development of sodium ion batteries, it is difficult to prepare carbon anode materials with high electrochemical performance, resulting in poor performance of sodium ion batteries. Relying on imported anode materials, it is difficult to meet the strategic development needs of domestic sodium ion batteries.
The coal-based material is mixed and ground with biomass carbon, and then carbonized and deaze-de-treated coal-based carbon anode material with high electrochemical properties is prepared. The method includes a first deaze treatment, a mixed grinding, a carbonization treatment and a second deaze treatment, through these steps, the impurities are removed and the microcrystal hybridization is promoted to form a hard carbon negative electrode with a pseudographite region.
It improves the electrochemical performance of coal-based carbon anode material, enhances the specific capacity, circulation performance and stability of sodium ion batteries, meets the high-performance needs of sodium ion batteries, and reduces production costs.
Smart Images

Figure CN119797324A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a coal-based carbon negative electrode material and a preparation method thereof and a sodium ion battery. Background Art
[0002] At present, the main energy supply in my country is still fossil energy such as coal, oil and natural gas. With the progress of human development, the disadvantages of fossil energy are becoming more and more apparent. People hope to use clean, efficient and renewable energy to replace fossil energy with limited reserves and environmental pollution. With the development of science and technology, people can initially use renewable energy such as solar energy, wind energy and hydropower, but instability, volatility and periodicity limit the further development of renewable energy. Energy storage technology is an important means to solve this problem.
[0003] Lithium-ion batteries have been widely used in portable electronic devices and electric vehicles in recent years due to their high energy density. However, the limited supply of lithium has restricted their application in large-scale energy storage technology. Sodium-ion batteries have the characteristics of abundant resource reserves, low cost, high energy conversion efficiency, and low maintenance costs. Therefore, they are considered to be a very promising large-scale energy storage technology solution. However, the radius of sodium ions is larger than that of lithium ions, and graphite negative electrode materials with mature lithium-ion battery technology and low cost are difficult to use in sodium-ion batteries. The core issue currently restricting the development of sodium-ion batteries is how to prepare negative electrode materials with high electrochemical performance. Domestic negative electrode materials for sodium-ion batteries mainly rely on imports, which is difficult to meet the strategic development needs of sodium-ion batteries. Therefore, the development of high-performance and low-cost carbon negative electrode materials for sodium-ion batteries is of great significance for sodium-ion batteries as large-scale commercial energy storage solutions. Summary of the invention
[0004] The present application provides a coal-based carbon negative electrode material and a preparation method thereof and a sodium ion battery to solve the following technical problem: how to improve the electrochemical performance of the coal-based carbon negative electrode material.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing a coal-based carbon negative electrode material, the method comprising:
[0006] Performing a first deashing treatment on the first coal-based material to obtain a second coal-based material;
[0007] The second coal-based material is mixed with biomass carbon and ground to obtain a mixed material with a set particle size;
[0008] Carrying out a carbonization treatment on the mixed material to cause microcrystalline hybridization of the mixed material to obtain a carbonized material;
[0009] The carbonized material is subjected to a second deashing treatment to obtain a coal-based carbon negative electrode material.
[0010] Optionally, the set particle size is 100nm to 1000nm.
[0011] Optionally, the grinding process parameters include: a grinding speed of 100 rad / min to 1000 rad / min, and a grinding time of 0.1 h to 12 h.
[0012] Optionally, the biomass carbon includes at least one of the following: starch, cellulose, and sucrose.
[0013] Optionally, the coal-based material includes at least one of the following: lignite, bituminous coal, and anthracite.
[0014] Optionally, it is characterized in that the weight ratio of the second coal-based material to the biomass carbon is 1:(0.01~3).
[0015] Optionally, the temperature of the carbonization treatment is 600°C to 1200°C.
[0016] In a second aspect, an embodiment of the present application provides a coal-based carbon negative electrode material, and the coal-based carbon negative electrode material is prepared by the method described in any embodiment of the first aspect.
[0017] In a third aspect, an embodiment of the present application provides a sodium ion battery, wherein the sodium ion battery comprises the coal-based carbon negative electrode material described in any one embodiment of the second aspect.
[0018] Optionally, the sodium ion battery meets the following performance:
[0019] The first-cycle discharge capacity is ≥304mAh / g, the first-cycle efficiency is ≥74%, the 50-cycle capacity retention rate is ≥88%, and the reversible capacity is ≥225mAh / g.
[0020] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0021] The preparation method of the coal-based carbon negative electrode material provided in an embodiment of the present application comprises: subjecting a first coal-based material to a first deashing treatment to obtain a second coal-based material; mixing and grinding the second coal-based material with biomass carbon to obtain a mixed material with a set particle size; subjecting the mixed material to a carbonization treatment to cause microcrystalline hybridization of the mixed material to obtain a carbonized material; subjecting the carbonized material to a second deashing treatment to obtain a coal-based carbon negative electrode material. The first coal-based material is subjected to the first deashing treatment, and the ash substances (impurity elements F, Na, Ca, Si, Fe, Ni) in the first coal-based material can be removed; the second coal-based material is mixed and ground with biomass carbon to obtain a mixed material with a set particle size, which can make the second coal-based material and biomass carbon pre-crosslinked during the grinding process, and the mixed material with the set particle size is conducive to promoting the occurrence of microcrystalline hybridization in the subsequent carbonization treatment; the mixed material is subjected to carbonization treatment, which can make the mixed material with the set particle size further undergo microcrystalline hybridization to form a large number of C=O and CO bonds, thereby forming a hard carbon negative electrode with a pseudo-graphite region, thereby expanding the interlayer space of the carbonized material, which is conducive to the storage and transportation of ions (sodium ions) and improving the electrochemical performance of the carbonized material; the carbonized material is subjected to the second deashing treatment, which can further remove the ash substances (impurity elements F, Na, Ca, Si, Fe, Ni) in the carbonized material, thereby reducing the influence of the ash substances on the electrochemical performance of the coal-based carbon negative electrode material. In summary, the electrochemical performance of the coal-based carbon negative electrode material is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0024] Figure 1 A schematic diagram of a process for preparing a coal-based carbon negative electrode material provided in an embodiment of the present application;
[0025] Figure 2 A schematic diagram of the appearance of a coal-based carbon negative electrode material provided in Example 3 of the present application;
[0026] Figure 3 This is a test graph of voltage-specific capacity of a sodium ion battery after 100 cycles of charge and discharge provided in Example 3 of the present application. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0028] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0029] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "include", "comprise", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, wherein a, b, c can be single or multiple, respectively. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula according to the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one by one to the proportional numbers in the proportional formula according to the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0031] In a first aspect, the present invention provides a method for preparing a coal-based carbon negative electrode material. Figure 1 A schematic diagram of a method for preparing a coal-based carbon negative electrode material provided in an embodiment of the present application; see Figure 1 , the method comprising:
[0032] S1, performing a first deashing treatment on the first coal-based material to obtain a second coal-based material;
[0033] In the embodiment of the present application, the first coal-based material is subjected to a first deashing treatment, and the ash substances (impurity elements F, Na, Ca, Si, Fe, Ni) in the first coal-based material can be removed. Exemplarily, step S1 includes: mixing the first coal-based material with a sub-molten salt of an alkali and heating them for reaction, performing solid-liquid separation on the slurry after the reaction, washing the solid product to neutrality, obtaining a first solid product, performing acid washing treatment on the obtained first solid product with an acid solution, performing solid-liquid separation on the slurry after the acid washing treatment, obtaining a second solid product, washing the second solid product to neutrality, and obtaining a second coal-based material.
[0034] S2, mixing and grinding the second coal-based material and biomass carbon to obtain a mixed material with a set particle size;
[0035] In some embodiments, the biomass carbon includes at least one of the following: starch, cellulose, and sucrose.
[0036] Biomass carbon refers to a carbon-containing product formed by a thermochemical conversion (such as pyrolysis) process of biomass (such as organic matter such as plants and animal residues) under oxygen-deficient or oxygen-limited conditions. Biomass carbon is a solid carbonaceous material that retains most of the carbon elements in biomass. Biomass carbon is usually a black solid with a porous structure. The main component is carbon, and it also contains a small amount of hydrogen, oxygen, nitrogen and other elements. The chemical stability of biomass carbon is high and it is not easy to react with most chemical substances at room temperature. However, its surface contains abundant functional groups, such as hydroxyl, carboxyl, carbonyl, etc., which give biomass carbon a certain chemical reactivity. In the embodiment of the present application, illustratively, the biomass carbon can be a combination of one or more of starch, cellulose, and sucrose.
[0037] In some embodiments, the coal-based material includes at least one of the following: lignite, bituminous coal, and anthracite.
[0038] Coal-based materials are materials prepared by various physical and chemical processing methods using coal as the main raw material. Coal is a complex organic rock containing multiple elements such as carbon, hydrogen, oxygen, nitrogen, and sulfur. The composition and structure of these elements provide the basis for the diversity of coal-based materials. In the embodiment of the present application, the coal-based material can be a combination of one or more of lignite, bituminous coal, and anthracite.
[0039] In some embodiments, the set particle size is 100 nm to 1000 nm.
[0040] In some embodiments, the grinding process parameters include: a grinding speed of 100 rad / min to 1000 rad / min, and a grinding time of 0.1 h to 12 h.
[0041] In the embodiment of the present application, the second coal-based material is mixed and ground with biomass carbon to obtain a mixed material with a set particle size, so that the second coal-based material and biomass carbon are pre-crosslinked during the grinding process, and the mixed material with the set particle size is conducive to promoting the occurrence of microcrystalline hybridization in the subsequent carbonization treatment. Exemplarily, the set particle size can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, etc.
[0042] The grinding speed can be 100 rad / min to 1000 rad / min, and the grinding time can be 0.1 h to 12 h, so that the second coal-based material and the biomass carbon are fully ground, the particle sizes of the second coal-based material and the biomass carbon are reduced to reach the set particle size, and the mixing uniformity of the ground materials is improved, thereby increasing the contact area between the second coal-based material and the biomass carbon, which enhances their activity in the chemical reaction and causes the second coal-based material and the biomass carbon to be pre-crosslinked during the grinding process. Exemplarily, the grinding speed can be 100rad / min, 200rad / min, 300rad / min, 400rad / min, 500rad / min, 600rad / min, 700rad / min, 800rad / min, 900rad / min, 1000rad / min, etc.; the grinding time can be 0.1h, 0.2h, 0.3h, 0.4h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.
[0043] In some embodiments, the weight ratio of the second coal-based material to the biomass carbon is 1:(0.01-3).
[0044] In the embodiment of the present application, the weight ratio of the second coal-based material to the biomass carbon is 1:(0.01-3), which can make the subsequent coal-based carbon negative electrode material have the best electrochemical performance. If the weight ratio of the second coal-based material to the biomass carbon is lower than 1:3, the second coal-based material and the biomass carbon may cause a side reaction during the subsequent carbonization process, thereby causing the electrochemical performance of the coal-based carbon negative electrode material to decrease; if the weight ratio of the second coal-based material to the biomass carbon is higher than 1:0.01, the microcrystalline hybridization process of the second coal-based material and the biomass carbon during the subsequent carbonization process may be weak, and the number of C=O and CO bonds may be small, thereby causing the electrochemical performance of the coal-based carbon negative electrode material to fail to meet the standard. Exemplarily, the weight ratio of the second coal-based material to biomass carbon is 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:1, 1:1.3, 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.5, 1:2.8, 1:3, etc.
[0045] S3, carbonizing the mixed material to cause microcrystalline hybridization of the mixed material to obtain a carbonized material;
[0046] In some embodiments, the temperature of the carbonization treatment is 600°C to 1200°C.
[0047] In the embodiment of the present application, the mixed material is subjected to carbonization treatment, which can make the mixed material with a set particle size further undergo microcrystalline hybridization, forming a large number of C=O and CO bonds, thereby forming a hard carbon negative electrode with a pseudo-graphite region, thereby expanding the interlayer space of the carbonized material, which is beneficial to the storage and transportation of ions and improving the electrochemical performance of the carbonized material. The carbonization temperature can be 600°C to 1200°C, which can make the subsequent coal-based carbon negative electrode material have the best electrochemical performance. If the temperature of the carbonization treatment is greater than 1200°C, it may cause the second coal-based material and biomass carbon to have side reactions in the subsequent carbonization process, thereby causing the electrochemical performance of the coal-based carbon negative electrode material to decrease; if the temperature of the carbonization treatment is less than 600°C, the temperature of the carbonization treatment is not enough, which may cause the second coal-based material and biomass carbon in the subsequent carbonization process. The microcrystalline hybridization process is weak, and the number of C=O and CO bonds is small, resulting in the electrochemical performance of the coal-based carbon negative electrode material not meeting the standard. In addition, in the carbonization treatment, the temperature rise rate of the carbonization treatment may be 1° C. / min to 10° C. / min, and the time of the carbonization treatment may be 1 h to 5 h.
[0048] S4. Perform a second deashing treatment on the carbonized material to obtain a coal-based carbon negative electrode material.
[0049] In the embodiment of the present application, the carbonized material is subjected to a second deashing treatment, and the ash substances (impurity elements F, Na, Ca, Si, Fe, Ni) in the carbonized material can be further removed, thereby reducing the influence of the ash substances on the electrochemical properties of the coal-based carbon negative electrode material. Exemplarily, step S4 includes: mixing and stirring the carbonized material with an acid solution to obtain a first slurry; washing the solid product obtained by solid-liquid separation of the first slurry to neutrality, and then mixing and stirring the solid product with an alkali solution to obtain a second slurry; washing the solid product obtained by solid-liquid separation of the second slurry to neutrality to obtain a coal-based carbon negative electrode material. Among them, the acid solution can be a combination of one or more of sulfuric acid, nitric acid, hydrofluoric acid, and hydrochloric acid, and the alkali solution can be a combination of one or more of sodium hydroxide, potassium hydroxide, and calcium hydroxide.
[0050] In summary, the method for preparing a coal-based carbon negative electrode material provided in the embodiment of the present application has the following advantages:
[0051] 1. First deashing treatment: remove the ash substances (such as impurity elements such as F, Na, Ca, Si, Fe, Ni, etc.) in the first coal-based material. These ash impurities in the coal-based material will affect the subsequent reaction process and the electrochemical properties of the final coal-based carbon negative electrode material. Chemical or physical methods are usually used for deashing. Chemical methods may involve the use of acid, alkali and other reagents to react chemically with ash impurities to convert them into soluble or easily separable substances;
[0052] 2. Mixing and grinding: During the grinding process, the second coal-based material is pre-crosslinked with the biomass carbon. This is because the mechanical effects such as constant friction and collision between the particles during the intense grinding process cause their surface molecules or atoms to interact with each other, which may form some chemical bonds or physical adsorption effects. Obtaining a mixed material with a set particle size is extremely critical for subsequent carbonization treatment. The appropriate particle size can increase the specific surface area of the material, making the subsequent reaction more sufficient. The smaller particle size means that more reactive sites are exposed. During the carbonization process, these sites can better participate in the microcrystalline hybridization reaction and promote the formation of C=O and CO bonds;
[0053] 3. Carbonization treatment: During the carbonization process, the mixed material undergoes complex chemical reactions under high temperature. The chemical bonds between the second coal-based material and the biomass carbon in the mixed material with a set particle size are further rearranged and formed, and microcrystalline hybridization occurs. The carbon structure in the biomass carbon is intertwined with the carbon structure in the coal-based material to form a microcrystalline region. At the same time, due to the formation of carbon-oxygen bonds (C=O, CO), the local chemical environment of the carbonized material is changed, making the structure of the carbonized material more complex, forming a hard carbon negative electrode with a pseudo-graphite region; the formed pseudo-graphite region and a large number of C=O and CO bonds have an important influence on the electrochemical performance. The pseudo-graphite region has good conductivity and can improve the electron transport capacity of the electrode material. The presence of C=O and CO bonds can improve the storage and transport performance of sodium ions in the electrode material through interaction with sodium ions. The expansion of the interlayer space is conducive to the embedding and extraction of sodium ions, thereby improving the charge and discharge capacity and rate performance of the material, so that the carbonized material has better electrochemical performance and is more suitable for use as a coal-based carbon negative electrode material in sodium ion batteries;
[0054] 4. Second deashing treatment: Although some ash impurities have been removed in the first deashing treatment, new impurities may be introduced during the carbonization process or impurities that have not been completely removed before may remain. The second deashing treatment can further remove the ash substances (such as F, Na, Ca, Si, Fe, Ni, etc.) in the carbonized material, thereby ensuring that the obtained coal-based carbon negative electrode material has low ash impurities. Coal-based carbon negative electrode materials with low ash impurities can effectively reduce the adverse effects of ash substances on their electrochemical properties. Ash impurity elements may cause side reactions during the electrochemical cycle. Removing these impurities through the second deashing treatment can improve the performance of coal-based carbon negative electrode materials in practical applications, making them more reliable and stable.
[0055] In a second aspect, an embodiment of the present application provides a coal-based carbon negative electrode material, and the coal-based carbon negative electrode material is prepared by the method described in any embodiment of the first aspect.
[0056] The coal-based carbon negative electrode material is realized based on the preparation method of the above-mentioned coal-based carbon negative electrode material. The specific steps of the preparation method of the coal-based carbon negative electrode material can refer to the above-mentioned embodiment. Since the coal-based carbon negative electrode material adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0057] In a third aspect, an embodiment of the present application provides a sodium ion battery, wherein the sodium ion battery comprises the coal-based carbon negative electrode material described in any one embodiment of the second aspect.
[0058] In some embodiments, the sodium ion battery meets the following performance:
[0059] The first-cycle discharge capacity is ≥304mAh / g, the first-cycle efficiency is ≥74%, the 50-cycle capacity retention rate is ≥88%, and the reversible capacity is ≥225mAh / g.
[0060] In the embodiment of the present application, the above-mentioned coal-based carbon negative electrode material is particularly suitable for the negative electrode of a sodium ion battery. The coal-based carbon negative electrode material has a large number of C=O and CO bond structures, forming a hard carbon negative electrode with a pseudo-graphite region, which expands the interlayer space of the coal-based carbon negative electrode material and facilitates the storage and transportation of sodium ions, thereby enhancing the performance of the sodium ion battery assembled with the coal-based carbon negative electrode material and improving the specific capacity and cycle performance of the sodium ion battery.
[0061] The sodium ion battery is realized based on the above-mentioned coal-based carbon negative electrode material. The specific preparation method of the coal-based carbon negative electrode material can refer to the above-mentioned embodiment. Since the sodium ion battery adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0062] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.
[0063] Example 1
[0064] A method for preparing a coal-based carbon negative electrode material, specifically comprising:
[0065] The first coal-based material is subjected to a first deashing treatment to obtain a second coal-based material; specifically, 200 g of lignite, 300 g of potassium hydroxide and 100 g of deionized water are mixed, heated and reacted and stirred (120° C., stirring for 3 hours), the slurry after the reaction is subjected to solid-liquid separation, the solid product is washed to neutrality to obtain a first solid product, the first solid product is subjected to an acid wash treatment using 5wt% hydrochloric acid (the mass ratio of hydrochloric acid to the first solid product is 1:1, 90° C., stirring for 5 hours), the slurry after the acid wash treatment is subjected to solid-liquid separation to obtain a second solid product, the second solid product is washed to neutrality with deionized water to obtain a second coal-based material;
[0066] The second coal-based material and the biomass carbon are mixed and ground to obtain a mixed material with a set particle size; specifically: 10 g of starch and 90 g of the second coal-based material are evenly mixed, put into a planetary mill, the speed is set to 500 rad / min, the grinding time is 6 hours, and a mixed material with a set particle size of 100 nm to 1000 nm is obtained;
[0067] The mixed material is subjected to carbonization treatment to obtain a carbonized material; specifically, 80 g of the mixed material is placed in a quartz boat, which is placed in a tubular furnace with nitrogen protection, and the carbonization heating program is set as follows: the heating rate is 5°C / min, the temperature is raised to 1100°C for carbonization treatment, the carbonization treatment time is 2 hours, and the temperature is naturally lowered after the carbonization program is completed to obtain a carbonized material;
[0068] The carbonized material is subjected to a second deashing treatment to obtain a coal-based carbon negative electrode material; specifically, 40 g of the carbonized material is put into a polytetrafluoroethylene beaker, 300 ml of 5 mol / l hydrochloric acid is added to the beaker, and the mixture is stirred at room temperature for 10 hours at a rotation speed of 500 rpm to obtain a first slurry; the solid product obtained by solid-liquid separation of the first slurry is washed with deionized water to be neutral, and then 300 ml of 0.2 wt% sodium hydroxide is added to the solid product, and the mixture is stirred at 50°C for 6 hours at a rotation speed of 250 rpm to obtain a second slurry; the solid product obtained by solid-liquid separation of the second slurry is washed with deionized water to be neutral to obtain a coal-based carbon negative electrode material.
[0069] Example 2
[0070] Based on the disclosure of Example 1, Example 2 differs from Example 1 in that: 20 g of starch and 80 g of the second coal-based material.
[0071] Example 3
[0072] Based on the disclosure of Example 1, Example 3 differs from Example 1 in that: 30 g of starch and 70 g of the second coal-based material.
[0073] Example 4
[0074] Based on the disclosure of Example 1, Example 4 differs from Example 1 in that: 40 g of starch and 60 g of the second coal-based material.
[0075] Comparative Example 1
[0076] Based on the disclosure of Example 1, the difference between Comparative Example 1 and Example 1 is that: 0g of starch and 100g of the second coal-based material.
[0077] The coal-based carbon negative electrode materials for sodium ion batteries prepared in the above Examples 1 to 4 and Comparative Example 1 were tested, and the prepared sodium ion batteries were subjected to electrochemical performance tests. The test results are shown in Table 1 below.
[0078] Table 1 Electrochemical performance test results of sodium ion batteries
[0079]
[0080] As can be seen from Table 1, the coal-based carbon negative electrode material prepared by the method of the embodiment of the present application is assembled into a sodium ion battery, which has a high first discharge capacity, a high first cycle efficiency, a high capacity retention rate after 50 cycles of the battery, and a high reversible capacity, which meets the requirements for the use of sodium ion batteries. In addition, the preparation method is simple, the cost is low, and it is easy to promote large-scale industrialization. Figure 2 This is a schematic diagram of the appearance of a coal-based carbon negative electrode material provided in Example 3 of the present application; see Figure 2 , indicating that Example 3 successfully prepared a coal-based carbon negative electrode material for a sodium ion battery, which is black and has a porous structure, and the porous structure is conducive to the penetration of the electrolyte in the sodium ion battery. Figure 3 This is a test diagram of voltage-specific capacity of a sodium ion battery with 100 cycles of charge and discharge provided in Example 3 of the present application; see Figure 3 , indicating that the coal-based carbon negative electrode material of Example 3 assembled into a sodium ion battery has an initial discharge capacity of 335 mAh / g, a first cycle efficiency of 77%, a 50-cycle capacity retention rate of 91%, and a reversible capacity of 258 mAh / g.
[0081] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:
[0082] (1) Coal-based materials and biomass carbon are mixed and ground sufficiently to allow the two to be pre-crosslinked, and the particle size of the sample after grinding is between 100nm and 1000nm; then, the pre-crosslinked mixed material is further subjected to a carbonization process to undergo microcrystalline hybridization to form a large number of C=O and CO bonds, thereby forming a hard carbon negative electrode with a pseudo-graphite region, thereby expanding the interlayer space of the carbonized material to facilitate the storage and transportation of sodium ions; finally, the carbonized material is subjected to a second deashing treatment, thereby enhancing the performance of a sodium ion battery assembled from a coal-based carbon negative electrode material, and improving the specific capacity and cycle performance of the sodium ion battery;
[0083] (2) The method for preparing coal-based carbon negative electrode materials provided in the embodiments of the present application has a simple preparation process, low equipment requirements, low cost, and the prepared sodium ion battery has a high specific capacity and excellent cycle performance. It can effectively solve the problem of poor performance and poor stability of coal-based negative electrode materials for sodium ion batteries, and is expected to promote the large-scale commercial energy storage application of sodium ion batteries.
[0084] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a coal-based carbon negative electrode material, the method comprising: Performing a first deashing treatment on the first coal-based material to obtain a second coal-based material; Mixing and grinding the second coal-based material with biomass carbon to obtain a mixed material with a set particle size; Carrying out a carbonization treatment on the mixed material to cause microcrystalline hybridization of the mixed material to obtain a carbonized material; The carbonized material is subjected to a second deashing treatment to obtain a coal-based carbon negative electrode material.
2. The method according to claim 1, characterized in that The set particle size is 100nm to 1000nm.
3. The method according to claim 1 or 2, characterized in that: The grinding process parameters include: a grinding speed of 100 rad / min to 1000 rad / min, and a grinding time of 0.1 h to 12 h.
4. The method according to claim 1, characterized in that The biomass carbon includes at least one of the following: starch, cellulose, and sucrose.
5. The method according to claim 1, characterized in that The coal-based material includes at least one of the following: lignite, bituminous coal, and anthracite.
6. The method according to claim 1, 4 or 5, characterized in that: The weight ratio of the second coal-based material to the biomass carbon is 1:(0.01-3).
7. The method according to claim 1, characterized in that The temperature of the carbonization treatment is 600°C to 1200°C.
8. A coal-based carbon negative electrode material, wherein the coal-based carbon negative electrode material is prepared by the method according to any one of claims 1 to 7.
9. A sodium ion battery, comprising the coal-based carbon negative electrode material according to claim 8.
10. The sodium ion battery according to claim 9, characterized in that: The sodium ion battery meets the following performances: first-cycle discharge capacity ≥304 mAh / g, first-cycle efficiency ≥74%, 50-cycle capacity retention rate ≥88%, and reversible capacity ≥225 mAh / g.
Citation Information
Patent Citations
Sodium ion battery negative electrode material and preparation method thereof
CN114613964A
Hard carbon negative electrode material for sodium battery as well as preparation method and application of hard carbon negative electrode material
CN117393758A
Preparation method and application of coal-based functional carbon material
CN117623274A
Preparation method of coal-based hard carbon negative electrode material as well as product and application of coal-based hard carbon negative electrode material
CN117945385A
Lignite-based hard carbon material for sodium ion battery negative electrode
CN118419893A